Fluoride ion emission, shear bond strength, and adhesive remnant index of calcium fluoride nanoparticles-containing orthodontic primer: an In Vitro study - Azren Nurin Afrina Syasya; Krishnan Sunittha Gopala; Lau May Nak; Kamarudin Yasmin; Lim Ghee Seong; Salleh Nosizana Mohd; Manan Ninie Suhana Abdul (Australasian Orthodontic Journal, 2025)
This study investigated fluoride ion emission, shear bond strength (SBS), and the adhesive remnant index (ARI) of orthodontic primers containing varying percentages of calcium fluoride nanoparticles (nCaF2).